Choosing sensitive agricultural products in trade negotiations - Jean, Sébastien; Laborde Debucquet, David; Martin, Will (International Food Policy Research Institute, 2008)
The formula approach used in many trade negotiations involves large formula cuts in high tariffs, with flexibilities that allow smaller cuts for selected products. Difficulties in evaluating the effects of these exceptions can create major problems. We use a political-economy welfare function and detailed data on the current WTO agricultural negotiations to assess the implications of this approach for welfare and for market access. We find that some previous rules of thumb greatly underestimate the impacts of such exceptions. Indeed, treating even a small number of tariff lines as sensitive and subjecting them to reduced cuts has a sharply adverse impact on welfare, and a smaller but still negative impact on market access.